Performance Evaluation of A Coconut Grating Machine - Adedipe Jide Olusegun; Yusuf I.O; Oyeleke O.S (Universitas Riau Kepulauan, 2026)
This study evaluates the performance of a locally fabricated coconut grating machine developed to address the inefficiencies, safety risks, and high labour demand associated with manual coconut grating. The machine operates on the principles of rotation and shearing. It comprises an electric motor, a stainless-steel grating shaft, a collector, and a reinforced support frame. A performance assessment was conducted using replicated trials to determine workability, throughput capacity, grating efficiency, and material loss. The evaluation involved measuring the initial and final weights of coconuts over twenty grating cycles. Results showed that the machine achieved a mean efficiency of 98%, attributed to its optimized shearing mechanism and minimal product loss (0.002 kg over an average grating duration of 59 s). Throughput capacity ranged from 0.16 to 0.77 kg/s, significantly surpassing manual grating operations. Graphical illustrations demonstrated that throughput increased with increasing material weight, while efficiency slightly declined at reduced loading; this could indicate that the machine performed optimally under moderate-to-high feed weights. Comparisons with manual grating revealed similar weight-loss trends but superior speed and safety advantages for the machine. Overall, the developed coconut grating machine offers a safe, efficient, and scalable solution for households and small-scale processors. For future improvements, focus could be on reducing clogging and enhancing adaptability to different coconut varieties.